Leibniz's metaphysics : its origins and development - Mercer, Christia (Cambridge University Press, 2001)
This book offers a major reassessment of Leibniz's metaphysics. Christia Mercer has exposed for the first time the underlying doctrines of Leibniz's philosophy. By analysing Leibniz's early works she demonstrates that the metaphysics of pre-established harmony developed many years earlier than previously believed and for reasons which have not been understood. As a result of this analysis she has unearthed a philosophical school that Leibniz scholars have not recognized. A much deeper understanding of some of Leibniz's key doctrines emerges. Moreover, since the Leibniz that is revealed here does not fit neatly into the standard accounts of the history of philosophy and science, Christia Mercer's study will prompt scholars to reconsider their basic assumptions about early modern philosophy and science.